The environmental effect of mass housing development in Abuja, Nigeria - Medugu, Nasiru Idris (2014)
This paper is aimed at assessing the effects of mass housing development in Lokogoma district of Abuja Phase II. This study was an inquisition into how mass housing development affects the environment as well as alters the design of the original master plan. The study examines the extent and magnitude on the social, economic and environmental aspect of the communities within the Phase II of the city. The scope of the study covers other areas of mass housing development within the Lokogoma district of the Abuja Phase III and emphasis is placed more on the private estate developers. Data on air quality, water quality, soil quality, vegetation and relief and landform were collected and assessed. A control point of 2km from the study location was picked to aid in the examination of the variation in the natural order. Air quality measurement was conducted using Gassman portable Digital Gas Monitors. Noise pollution test was carried out using a sound level meter. Physical and chemical contaminants in water were measured through water quality test. Other tests were also carried out to examine pollution from soil and vegetation. Impact assessment management matrix analysis was conducted to determine the environmental impacts through the construction of mass housing development. The results of the study revealed that air pollution and deforestation are two environmental problems affecting the study area and are having significant effect on the public health of the residents and causing flooding as well as soil erosion in the study area respectively. Thus, there is the need for urgent intervention from the authorities concerned in order to avoid or control the spread of these problems.